2002
DOI: 10.1152/ajprenal.00206.2001
|View full text |Cite
|
Sign up to set email alerts
|

NHE3 serves as a molecular tool for cAMP-mediated regulation of receptor-mediated endocytosis

Abstract: Receptor-mediated, clathrin-dependent endocytosis (RME) is important for macromolecular transport and regulation of cell-surface protein expression. Pharmacological studies have shown that the plasma membrane transport protein Na(+)/H(+) exchanger 3 (NHE3), which shuttles between the plasma membrane and the early endosomal compartment by means of clathrin-mediated endocytosis, contributes to endosomal pH homeostasis and endocytic fusion events. Furthermore, it is known that NHE3 is phosphorylated and inhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 39 publications
3
27
0
Order By: Relevance
“…This process occurs via a highly active and tightly regulated receptor-mediated pathway involving the albumin binding megalin/cubulin scavenger receptor (5,8,27). In addition to the receptor complex itself, the uptake of albumin appears to require the formation of a complex that includes the ion transporting proteins V-type H ϩ -ATPase, Na ϩ -H ϩ exchanger isoform 3 (NHE3), and the Cl Ϫ channel ClC-5 (11,20,27). The V-type H ϩ -ATPase plays a crucial role in the acidification of the endosomes/lysosomes required for the dissociation of albumin from the receptor (27), whereas NHE3 is thought to play a role in facilitating the initial acidification of the nascent endosome (11).…”
mentioning
confidence: 99%
“…This process occurs via a highly active and tightly regulated receptor-mediated pathway involving the albumin binding megalin/cubulin scavenger receptor (5,8,27). In addition to the receptor complex itself, the uptake of albumin appears to require the formation of a complex that includes the ion transporting proteins V-type H ϩ -ATPase, Na ϩ -H ϩ exchanger isoform 3 (NHE3), and the Cl Ϫ channel ClC-5 (11,20,27). The V-type H ϩ -ATPase plays a crucial role in the acidification of the endosomes/lysosomes required for the dissociation of albumin from the receptor (27), whereas NHE3 is thought to play a role in facilitating the initial acidification of the nascent endosome (11).…”
mentioning
confidence: 99%
“…Basal microvillus NHE3 was increased by myosin VI KD, whereas the secondmessenger-induced (FSH and CCH) decrease in microvillus NHE3 activity and amount was blocked. Because these two agents have been shown to stimulate endocytosis without altering the rates of exocytosis (Gekle et al, 2002;Lee-Kwon et al, 2003;Musch et al, 2007;Zachos et al, 2013), we propose that both basal and stimulated endocytosis require myosin VI. Additionally, because EGF treatment of myosin VI KD cells still led to an increase in microvillar NHE3 activity, our results further indicate that myosin VI is not involved in the stimulated exocytosis of NHE3 in the Na + -absorptive cell.…”
Section: Discussionmentioning
confidence: 92%
“…It has been suggested that increased levels of cAMP reduce albumin uptake by inhibiting NHE3 (11). cAMP inhibits NHE3 via an NHERF1-ezrin-protein kinase A complex (53) and basal level phosphorylation of NHE3 by protein kinase A is reported in proximal tubule cells (54).…”
Section: Discussionmentioning
confidence: 99%
“…The percent inhibition of total albumin uptake was 21.9 Ϯ 3% for the pSHAG-FF and 21.8 Ϯ 3% when NHERF1 was silenced (n ϭ 3). uptake by OK cells is inhibited by cAMP, an effect that has been attributed to inhibition of NHE3 (11). We therefore investigated whether 8-Br-cAMP could inhibit the increase in albumin uptake observed following silencing of NHERF1.…”
Section: Roles Of Nherf2 and Nherf1 In Albumin Endocytosismentioning
confidence: 99%
See 1 more Smart Citation